The Activity of Lipase From Jatropha Seed (Jatropha Curcas L.) And Its Application On Hydrolysis of Castor Oil In Organic Solvent - Faradis, Taritsu Hazal; Srihardyastutie, Arie; Iftitah, Elvina Dhiaul (Graduate School, Universitas Brawijaya, 2022)
Jatropha curcas L. is one of the seed plants that have lipase activity and can work well in hydrolysis reactions and chemical synthesis. This study aims to determine lipase activity that reacts with castor oil in organic solvents. In this research, organic solvents, especially hydrophobic solvents, were used in the hydrolysis reaction to increase lipase's catalytic activity. The organic solvent used has a hydrophobicity level between 2 and 4, namely hexane. The research stages consisted of lipase isolation, lipase assay, the effect of adding metal ions assay, and analysis of the compound of castor oil. The results showed that jatropha seeds had lipase activity in crude of 0.603 U/mL and increased to 0.911 U/mL after the addition of K+. The result of hydrolysis and transesterification of castor oil by lipase is ricinoleic acid (4,58%) and methyl ricinoleic (11,67%), and the concentration of ricinoleic acid (17.09%) and methyl ricinoleic (60.83%) were increased after addition of K+. The esterification reaction produces alkyl ester compounds such as methyl palmitate, ethyl pentadecanoate, methyl linoleate, methyl oleate, and methyl stearate. The lipase isolated from jatropha seeds not only catalyzes the hydrolysis reaction but also catalyzes chemical synthesis reactions such as esterification and transesterification. Keywords: lipase enzyme, Jatropha seeds, isolation, biocatalyst, hexane.